ANALYSIS OF THE USE OF NON-CASH TRANSACTIONS USING DIGITAL APPLICATIONS IN THE TIME OF COVID-19 AT PT. PAWNTOWN SHARIA UPS SIBUHUAN - Nuraini, Nuraini; Siregar, Sulaiman Efendi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research was motivated by the use of non-cash transactions using digital applications which decreased during the Covid-19 period where the use of digital Islamic pawnshop applications before Covid-19 increased while during the Covid-19 period their use decreased, because there were still many customers who did not know how to use digital Islamic pawnshop applications . The formulation of the research problem is how to use the digital sharia pawnshop application during the Covid-19 period at PT. Pegadaian Syariah UPS Sibuhuan, how is the customer's response to the digital sharia pawnshop application. The purpose of this study was to determine the use of digital sharia pawnshop applications during the Covid-19 period at PT. UPS Syariah Pawnshop is busy and to find out the response from customers to the digital sharia pawnshop application.The theory presented in this study relates to the theory of interest in using, satisfaction, service quality, non-cash transactions, digital sharia pawnshop applications. According to Arianto's experts, service quality can be interpreted as focusing on meeting needs and requirements, as well as on timeliness to meet customer expectations. Service quality is also measured by how well the level of service provided is in accordance with customer expectations.This research is a qualitative research with descriptive data sources used are primary data and secondary data, while the data collection techniques of this research are interviews, observation and documentation.The results of this study concluded that the use of non-cash transactions using the digital Islamic pawnshop application during the Covid-19 period decreased due to lack of application promotion, the registration process was not guided by Islamic pawnshops, the target was only pawn financing (rahn), customer responses were also initially enthusiastic about However, due to the lack of education from pawnshops about digital sharia pawnshop applications, customers prefer to come in person to make transactions, network constraints, and lack of customer knowledge in using digital-based services.